The BATANG KEMUMU (Colacasia gigantea cv) SEBAGAI BAHAN BAKU OBAT ALAMI ANTIBAKTERI DAN ANTIKANKER - Hesti Marliza; Trie Yuni Elfasyari Elfasyari; Faziyana; Sarina Sembiring Milala (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2021)
Kemumu (Colocasia gigantea cv) is a type of taro whose stems and leaves are edible. Kemumu belongs to the type of taro whose properties and phytochemical content, in particular, have not been widely reported. This study aims to determine the phytochemical content of kemumu stem as well as antibacterial bioactivity test and cytotoxic test (anticancer initial test) which can be used as raw materials for natural medicine. The stem is extracted using three types of solvents with different levels of polarity, n-Hexane, Ethyl acetate, and Ethanol. Antibacterial activity test uses agar diffusion method with some 20%, 40%, and 60% concentrations. Cytotoxic activity was tested by the Brine Shrimps Lethality Test (BSLT) method. Phytochemical test results are known that the kemumu extract contains secondary metabolites such as flavonoids, alkaloids, tannins, terpenoids, and steroids. The ethyl acetate extract contains flavonoids, tannins, terpenoids, and steroids. Antibacterial activity was found in ethyl acetate extract with a concentration of 40% with an inhibition zone of 17.5 mm. The highest LC50 value was also in the ethyl acetate extract of kemumu, which was 7.14 ppm. This value indicates a high level of toxicity so that ethyl acetate extract of kemumu acts as an antibacterial and anticancer.